Structural analysis and cytokine-induced activity of gelling sulfated polysaccharide from the cystocarpic plants of Ahnfeltiopsis flabelliformis. (20th October 2016) - Kravchenko, Anna O.; Anastyuk, Stanislav D.; Sokolova, Ekaterina V.; Isakov, Vladimir V.; Glazunov, Valery P.; Helbert, William; Yermak, Irina M.
Graphical abstract: Highlights: Gelling carrageenan from cystocarpic plants of A. flabelliformis is iota/kappa-type. The polysaccharide contains minor amounts of beta-, nu- and mu-carrageenans. Xylose substitutes OH-group at C-6 of 1, 3-linked β-d -galactose in agaran structures. Carrageenans increase cytokines synthesis depending on their molecular weight. Abstract: Gelling sulfated polysaccharide from the cystocarpic plants of Ahnfeltiopsis flabelliformis was studied. According to FT-IR and NMR spectroscopy data, the polysaccharide was found to be iota/kappa-carrageenan with iota- and kappa-type units in a 2:1 ratio containing beta-carrageenan units and minor amounts of nu- and mu-carrageenans. The HPLC and ESI MS/MS data of enzymatic hydrolysis products revealed that the main components of the polymer chain are iota-carrabiose, iota-carratetraose and hybrid tetra- and hexasaccharides consisting of kappa- and iota-units. Xylose was a substituent of a hydroxyl group at C-6 of 1, 3-linked β-d -galactose in the total polysaccharides. It was shown that the ability of carrageenans to increase the synthesis of cytokines depended on their molecular weight. The polysaccharide induced the synthesis of the anti-inflammatory cytokine IL-10, whereas oligosaccharides increased the synthesis of both pro- and anti-inflammatory cytokines at high concentrations.